☆Symposium: Imaging modalities for drug-related osteonecrosis of the jaw (5), utility of bone scintigraphy and 18F-FDG PET/CT in early detection and risk assessment of medication-related osteonecrosis of the jaw (secondary publication) - Satoru Watanabe; Kenichi Nakajima; Seigo Kinuya (Elsevier, 2019)
Summary: Medication-related osteonecrosis of the jaw (MRONJ) is a significant side effect of antiresorptive and antiangiogenic drugs. Since MRONJ is intractable, early detection is the best way to limit progression. Bone scintigraphy and 18F- fluorodeoxyglucose positron-emission tomography can detect minimal and subclinical changes in bones earlier than conventional radiological modalities. A differential diagnosis including MRONJ is recommended when abnormally high uptakes are incidentally detected in the jaws of patients who have bone metastases. Quantitative analysis of uptakes, such as bone scan index of the jaw using neural network analysis and maximum standardized uptake value, could differentiate MRONJ from common dental diseases and be useful for the early detection and risk assessment of MRONJ. Keyword: Bone scintigraphy, Bone scan index, Computer-aided diagnosis, FDG PET, Osteonecrosis, Jaw